Passivhus i Kiruna : En studie av tekniska och ekonomiska förutsättningar - Hermansson, Emma (2012)
The energy issue has come to be a central part of the debate regarding the environment and climate changes. Since one third of the total use of energy in Sweden is related to housing, possibilities to save energy in this sector is large. This fact in combination with increased energy prices has made low energy buildings attractive. Building of passive houses, e. g. houses without a conventional heating system, have increased in Sweden. Although, there are still very few passive houses built in the north of Sweden, which may be due to uncertainty concerning the technical possibility and profitability for the clients.In this master thesis the technical and economical feasibility to build passive house in Kiruna are examined with the help of energy analysis and life cycle costs. The experiments are performed with help of the Passive House Planning Package where different alternatives are investigated. The results of the analysis have been cost estimated and compared with expected future energy prices using life cycle cost calculations.The life cycle cost calculations resulted in a variety of scenarios with different results dependent on the selected values of the input parameters. The results are not quite conclusive and the answer of the question if it is profitable to build a passive house in Kiruna is still uncertain. The uncertainties of the results are mainly due to difficulties in predicting energy prices, interest rates and inflation. However, energy savings occur in all scenarios which means that the profitability of the investments are only a matter of time. Validerat; 20120418 (anonymous)